PENGARUH DELEGATIVE LEADERSHIP, KOMUNIKASI DAN WORK LOYALTY TERHADAP PRODUKTIVITAS KERJA KARYAWAN: Studi Di RSUP Sanglah Denpasar - I Putu Bagus Suthanaya; Putu Agus Prayogi; I Ketut Eli Sumerta (Universitas Triatma Mulya, 2022)
This research was conducted based on the gap of previous research results (research gap) and differences in focus of discussion on delegative leadership, communication and work loyalty to employee work productivity. In addition, there is also a research problem regarding the high level of employee absenteeism at Sanglah Hospital Denpasar. This research was conducted at Sanglah General Hospital Denpasar population of 2,878 and a sample size of 144 employees. All data obtained from the distribution of the questionnaire is suitable for use, then analyzed using SPSS 25. The implication of this research is that delegative leadership can be improved by paying attention to indicators of decisions made jointly between leaders and subordinates. Communication can be improved by paying attention to indicators of superior discussions with subordinates. Work loyalty can be improved by paying attention to indicators of obeying the rules. Employee work productivity can be increased by paying attention to indicators of self-confidence.